Formulation and evaluation of body lotion containing ethanol extract peel of snake fruit (salacca zalacca (gaertn.) Voss) as a skin moisturizer - Meissi Kusuma; Nurul Azmi; Iin Ruliana Rohenti; Silfera Indra Yanti (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2026)
Maintaining healthy skin can be achieved through the use of moisturizing cosmetic preparations, such as body lotion, which serves to prevent the skin from becoming dry, rough, and dull. The peel of snake fruit (Salacca zalacca (Gaertn.) Voss) is known to contain flavonoid and phenolic compounds, which play a functional role in enhancing skin hydration and improving skin smoothness.. This study aims to formulate and evaluate the preparation of body lotion from ethanol extract peel of snake fruit. Peel of snake fruit extract was extracted by maceration method using 96% ethanol, then formulated into body lotion preparations with concentration variations of 0% (F0), 1% (F1), 3% (F2) and 5% (F3). Evaluation of the preparation includes organoleptic test, homogeneity, pH, spreadability, viscosity, stability, and irritation test using patch test method and moisture test using skin analyzer. The body lotion preparations obtained were purple to brown in color, homogeneous, the pH values were 6.21-6.57, the viscosity values werw 11530-18380 cP, and spreadability 6-6.4 cm. The stability test results at 5°C, 25°C, and 40°C temperatures for 4 weeks showed that all formulas were stable during storage and met the test requirements. The results of statistical analysis with the ANOVA method for all formulas at temperature 25°C did not have significant differences (p < 0, 05). All body lotion formulations demonstrated non-irritating properties and were effective in enhancing skin hydration levels. It can be concluded that the extract of peel of snake fruit can be successfully formulated into a body lotion preparation that complies with evaluation standards and exhibits significant potential as an effective skin moisturizing agent.